Portraying Teachers' Strategies in Teaching English for Young Learners - Muliyah, Pipit (Educalitra: English Education, Linguistics, and Literature Journal, 2023)
Teaching English to young learners in Indonesia remains a controversial topic among teachers and parents. Parents are particularly concerned about their children's progress in communication and interaction skills. Many English courses and programs are rapidly attracting children and their families from middle-class to upper-class backgrounds. However, there are concerns that teaching English in Indonesia emphasizes rote learning of rules and sentence development. Additionally, some teachers lack the necessary educational experience to effectively teach young learners. To address these concerns, a study was conducted using qualitative methods to explore perceptions and strategies in Teaching English to Young Learners (TEYL). The research subjects included teachers and parents. The study identified two critical factors that need attention in teaching English to young learners. The first factor is perception. Both teachers and parents believe that starting English education at a young age leads to greater knowledge acquisition. Teacher perception received the highest score, with 74 out of 80, while parents' perception scored 57 out of 70. The second factor is strategy. Teachers are encouraged to implement appropriate strategies based on the specific conditions and situations of the school. Video-based instruction was found to be the most suitable method for student engagement and character development. Overall, this study highlights the importance of addressing perceptions and employing effective strategies when teaching English to young learners in Indonesia. By considering these factors, educators can create a more productive and engaging learning environment for children.